Engineering Thresholds : an Approach to Curriculum Renewal : Guide for Engineering Educators on Curriculum Renewal using Threshold Concepts. - Male, Sally (Office for Learning and Teaching, 2012)
Guide for engineering educators produced as part of a project that focused on essential and critical foundational concepts that substantively define the thresholds or portals for engineering students of any discipline. These concepts are the ones that 'open up' the terrain and facilitate learning of students in upper years. A unique opportunity arose at UWA to design an engineering program based on an understanding of these concepts. Engineering students will in future take an Engineering Science Major as part of a Bachelor of Science and within this will be a common foundational program. It was proposed to design the new foundation program based on threshold concept theory and the study of foundational thresholds. Workshops were held with engineering lecturers across Australia to consider these and other thresholds in the basic levels of engineering degrees. A map of introductory level concepts and suggestions for helping students navigate through them was developed for continual and iterative improvement, accessible to all.